Dietary Supplementation of Purified Amino Acid Derived from Animal Blood on Immune Response and Growth Performance of Broiler Chicken - T. G. Wandita; N. Joshi; I. S. Nam; S. H. Yang; H. S. Park; S. G. Hwang (Faculty of Animal Science, Bogor Agricultural University, 2018)
The existences of protein are important to supply nutritional requirements and to support optimal growth performance in modern broiler chicken. The present experiment was conducted to evaluate the effect of purified amino acid (PAA) isolated from animal blood on growth performance and immune response. A total of one hundred of 1-day old broiler chicken were used in the experiment, following a completely randomized design of 4 groups of treatment differed in concentrations of PAA supplementation (T1: control, no PAA addition; T2: 0.05%; T3: 0.1%; and T4: 0.5%) with 4 replicates for each group. Levels of various cytokines, such as IgA, IgG, interleukin (IL)-2, IL-6, tumor necrosis factor α, and interferon γ, were analyzed using an ELISA kit. Insulin-like growth factor 1, an important growth hormone, was also examined using an ELISA kit. The present result showed feed efficiency and average daily feed intake of broiler chicken increased significantly along with increasing concentrations of PAA (P<0.05). Plasma biochemical parameters and carcass traits were affected by supplementation of PAA. Insulin growth factor-1 levels were significantly increased along with increasing concentrations (until 0.5%) of PAA (P<0.05). Inflammatory marker levels significantly differed between the control and treatment groups. These results indicate that purified amino acid isolated from animal blood affected the immune response and growth performance of broiler chicken. Furthermore, PAA can be used in feed supplementation for broiler chickens without causing health issues. It suggests that the beneficial impacts of PAA on immune responses, as well as blood characteristics, may improve broiler performance.